RANCANGAN DAN PENERAPAN METODE FIXED TIME BASE MAINTENANCE PADA UNIT AIR CONDITIONER SPLIT DI GEDUNG LABORATORIUM TEKNIK MESIN POLMANBABEL - Octadiansyah, Zacki; Mansyah, Subhan Benazir; Feriadi, Indra; Rodika (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
The Split Air Conditioner (AC) unit in the PolmanBabel Mechanical Engineering Laboratory Building is used as a room cooling device for practicum students, lecturers and PLP. With such a high usage time (average usage 10 hours to 24 hours) there is a lot of possibility of damage occurring. To reduce and overcome this problem, it is planned to design a preventive maintenance system for Split AC units at the PolmanBabel Mechanical Engineering Laboratory. The design of this preventive maintenance system is based on data from several stages, starting from Split AC inventory data, interview data, Split AC maintenance data and manual book. The results of the preventive maintenance system design for Split ACs include various important elements, starting from Split AC preventive maintenance maintenance plan data, Split AC preventive maintenance schedules, maintenance checklist cards, control cards, historical maintenance or damage cards and Split AC preventive maintenance procedures. The aim of this preventive maintenance system design is so that it can be understood and understood well by equipment managers, implementers and users, so that this preventive maintenance system design can be implemented and applied to Split AC units at the PolmanBabel Mechanical Engineering Laboratory. By implementing this preventive maintenance system, it is hoped that the Split AC units at the PolmanBabel Mechanical Engineering Laboratory can operate much better so that they have a longer service life and reduce the damage that occurs.